1990
DOI: 10.1016/0304-3959(90)91164-e
|View full text |Cite
|
Sign up to set email alerts
|

Transsynaptic degeneration in the superficial dorsal horn after sciatic nerve injury: effects of a chronic constriction injury, transection, and strychnine

Abstract: The lumbar and cervical spinal dorsal horns of adult rats with a chronic (8 days) constriction injury of the sciatic nerve on one side (and a sham operation on the other) were examined for signs of transsynaptic degeneration. The incidence of neurons with signs of degeneration (pyknosis and hyperchromatosis; 'dark neurons') was significantly increased in the lumbar dorsal horn on both sides. The ipsilateral lumbar increase was significantly greater than the contralateral increase. There was no increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(113 citation statements)
references
References 29 publications
1
109
1
2
Order By: Relevance
“…Although the antiinflammatory effects of corticosteroids could be beneficial under such circumstances, our results indicate that an unexpected adverse effect of GR activation within the CNS could contribute to the neural mechanisms of neuropathic pain behaviors. Second, neuronal degeneration within the spinal cord dorsal horn occurs after peripheral nerve injury (Sugimoto et al, 1990;Mao et al, 1997;Moore et al, 2002), and recent studies have indicated detrimental effects of GR agonists on NMDA-induced neuronal degeneration (Abraham et al, 2000) and in neuronal apoptosis during autoimmune-related inflammation (Diem et al, 2003). Thus, actions of central GRs could potentially worsen neuronal degeneration induced by peripheral nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although the antiinflammatory effects of corticosteroids could be beneficial under such circumstances, our results indicate that an unexpected adverse effect of GR activation within the CNS could contribute to the neural mechanisms of neuropathic pain behaviors. Second, neuronal degeneration within the spinal cord dorsal horn occurs after peripheral nerve injury (Sugimoto et al, 1990;Mao et al, 1997;Moore et al, 2002), and recent studies have indicated detrimental effects of GR agonists on NMDA-induced neuronal degeneration (Abraham et al, 2000) and in neuronal apoptosis during autoimmune-related inflammation (Diem et al, 2003). Thus, actions of central GRs could potentially worsen neuronal degeneration induced by peripheral nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral nerve injury produces apoptosis in the dorsal horn of the spinal cord (Sugimoto et al, 1990;Azkue et al, 1998;Whiteside and Munglani, 2001;Moore et al, 2002). In the superficial dorsal horn (laminas I-III), interneurons containing the transmitters GABA and glycine produce presynaptic and postsynaptic inhibition (Malcangio and Bowery, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this hypothesis includes the following observations: (1) loss of GABAergic or glycinergic inhibition within the dorsal horn leads to allodynia (Yaksh, 1989) and a lowered threshold for withdrawal reflexes (Sivilotti and Woolf, 1994); (2) there is a reduction in the level of GABA (Castro-Lopes et al, 1993;Ibuki et al, 1997;Eaton et al, 1998) and its synthesizing enzyme glutamate decarboxylase (Moore et al, 2002) in the ipsilateral dorsal horn after nerve injury; (3) "dark neurons" (Sugimoto et al, 1990) and apoptotic cells labeled with the terminal deoxynucleotidyl transferase-mediated biotinylated UTP nick end labeling (TUNEL) method (Kawamura et al, 1997;Azkue et al, 1998;Whiteside and Munglani, 2001;Moore et al, 2002;de Novellis et al, 2004) have been detected in the dorsal horn after various types of nerve injury; (4) a substantial reduction of primary afferent-evoked IPSCs in lamina II neurons has been reported in neuropathic models (but not after sciatic nerve transection) and was thought to result from a presynaptic mechanism involving reduction of GABA release (Moore et al, 2002). Although most studies of apoptosis in the dorsal horn after nerve injury have not identified the cell types involved, Moore et al (2002) reported that in the spared nerve injury (SNI) model (Decosterd and Woolf, 2000), Ïł10% of TUNEL-positive cells were neuronal.…”
Section: Introductionmentioning
confidence: 99%